Person-Centered Care Starts with Community-Centered Medical Education: Medical Education Must Answer the Call for Diversity - James David Katz; Emily Rose; Katlin Poladian; Karina D. Torralba (Social Medicine Publication Group, 2021)
Civil unrest is a call for realignment of values in all aspects of society, including medical education. Systematic difference in the treatment of groups of individuals concerning educational curricula has previously been highlighted in South Africa during student-led campaigns to decolonialize and diversify medical curricula1. Institutional resistance that results in a failure to account for the politics of identity or for pluralistic thinking,1 implies that the academic 'fence of unambiguous knowledge' not only creates an ivory tower but it may simultaneously insulate itself from community input and access. Confronting the tension between communal meaning (which sanctions a culturally relevant curriculum) and privileged meaning (which derives from a monolithic mindset) demands that educators recognize that the scientific method is only one 'way of knowing.' In this manuscript we ask: Who possesses authoritative medical meaning-making? And, Who confers authoritativeness to academia?